The student experience of a blended learning accounting course: a case study in Hong Kong - Lam, Yuet Ching Jeanne (2016)
The research is an inquiry into students’ learning experiences within a blended learning Accounting course in a sub-degree programme at a university in Hong Kong. In this course, the students were required to attend face-to-face classes and to participate in learning activities in the online platform. A case study research approach was adopted that involved 2 classes of 2 teachers and 80 students. Qualitative data were generated through classroom observations, online participation observations, student learning logs and reflections, student focus group interviews, student individual interviews, individual teacher interviews and an individual interview with the course leader. Thematic data analysis was used and a Community of Inquiry (CoI) model was used as a theoretical framework. The analysis showed that the students engaged in learning by integrating traditional and online learning activities and many of these were located within the social, cognitive and teaching presences within the CoI model. However, the students were found to be involved actively in non-prescribed activities that included the use of social network applications. The active learning exploration driven by students’ intrinsic motivation and the consequent collaborative learning among students using social media tools were not reflected in the CoI model. Hence, a new element of autonomy is proposed as an addition to the framework, to reveal the link of autonomous learning to the learning community. By extending the CoI framework, the contribution of this research is to provide a holistic model for the successful design and implementation of blended learning in higher education institutions.